2015
DOI: 10.1016/j.expneurol.2015.07.027
|View full text |Cite
|
Sign up to set email alerts
|

A balanced view of the cerebrospinal fluid composition and functions: Focus on adult humans

Abstract: In this review, a companion piece to our recent examination of choroid plexus (CP), the organ that secretes the cerebrospinal fluid (CSF), we focus on recent information in the context of reliable older data concerning the composition and functions of adult human CSF. To accomplish this, we define CSF, examine the methodology employed in studying the CSF focusing on ideal or near ideal experiments and discuss the pros and cons of several widely used analogical descriptions of the CSF including: the CSF as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
240
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(273 citation statements)
references
References 84 publications
1
240
0
5
Order By: Relevance
“…Subsequent studies introduced the term ‘glymphatic’ system to describe this paravascular circulation, and suggested that solute transport in the CNS occurs via CSF convective flow through the brain extracellular spaces, in a para-arterial to para-venous direction, regulated by aquaporin-4 (AQP4) water channels on astrocytes 37,38 . The proposed glymphatic mechanism, however, has not been supported by the latest studies 39–42 , and the convective, pressure-driven fluid flow of CSF from para-arterial to para-venous extracellular spaces throughout the parenchyma remains unproven 43–45,39,40 . Furthermore, deletion of Aqp4 in mice and rats does not impair the transport of fluorescent solutes from the subarachnoid space into the brain, which implies that water production by astrocyte end-feet does not have a role in the regulation of solute transport within parenchymal extracellular spaces 39 .…”
Section: The Bbb Molecular Architecturementioning
confidence: 99%
“…Subsequent studies introduced the term ‘glymphatic’ system to describe this paravascular circulation, and suggested that solute transport in the CNS occurs via CSF convective flow through the brain extracellular spaces, in a para-arterial to para-venous direction, regulated by aquaporin-4 (AQP4) water channels on astrocytes 37,38 . The proposed glymphatic mechanism, however, has not been supported by the latest studies 39–42 , and the convective, pressure-driven fluid flow of CSF from para-arterial to para-venous extracellular spaces throughout the parenchyma remains unproven 43–45,39,40 . Furthermore, deletion of Aqp4 in mice and rats does not impair the transport of fluorescent solutes from the subarachnoid space into the brain, which implies that water production by astrocyte end-feet does not have a role in the regulation of solute transport within parenchymal extracellular spaces 39 .…”
Section: The Bbb Molecular Architecturementioning
confidence: 99%
“…Notably, vitamin C and folate diffuse into the brain through the CSF (93,94). Many other ions and proteins are transported through the choroid plexus epithelium and diffuse from the CSF into the brain, where they affect neuronal function (94). More recently, the immune compartment in the meninges was implicated in neuronal function (75).…”
Section: Communication Between the Cns Compartmentsmentioning
confidence: 99%
“…CSF and its constituents can act directly on brain function. Notably, vitamin C and folate diffuse into the brain through the CSF (93,94). Many other ions and proteins are transported through the choroid plexus epithelium and diffuse from the CSF into the brain, where they affect neuronal function (94).…”
Section: Communication Between the Cns Compartmentsmentioning
confidence: 99%
“…However, ICP-MS elemental analysis of this human CSF samples is complex because of several reasons: i) first the concentration of the trace elements of interest is typically very low; ii) second, no CRMs are available; 8 iii) third, ICP-MS is prone to suffer from spectral as well as non-spectral interferences caused by the CSF matrix, 10,34 which may degrade accuracy. 12 Table 1 shows examples of possible spectral interferences when analysing CSF samples.…”
Section: -10mentioning
confidence: 99%